PERAN IBU RUMAH TANGGA DALAM PEREKONOMIAN KELUARGA STUDI KASUS DI DESA GUNEM KABUPATEN REMBANG - Dian Ayu Liana Dewi (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2015)
The role of a housewife who works in this study has the objective to improve theeconomy of the family. The purpose of this study was to determine the contribution ofthe role of a housewife who works in general, are able to support their families,especially in Gunem village, subdistrict Gunem, Gunem district. The problem in thisresearch is how the role of housewives in in Gunem village, subdistrict Gunem, Gunemdistrict in helping the family economy, in the context of the daily needs of their families.The method used the qualitative description of the approach. In the process of datacollection through direct observation, interviews with respondents and analyze existingdata, both primary and secondary data. The results of this study indicate that women ingeneral, housewives in particular has a strong role, morale high despite low income.Housewives who work can fill critical sectors role in the household. Such as education,health, economic and social. With the workings of a housewife, automatically becomes adouble role, namely as a housewife and a female worker. That is where the role ofhousewife devoted to the family and the role of women who produce social interactioncommunication with parties outside the family. From the sociological aspect in this studythe role and work of the spirit of the housewife in her efforts to help the welfare of thefamily is very high.Keywords: housewife, a dual role, working.